ANALISIS PENGARUH ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE BLACKBERRY (STUDI KASUS PADA MAHASISWA MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS SUMATERA UTARA MEDAN) - Tety Anggereni; Ami Dilham (Jurnal Media Informasi Manajemen, 2013)
Abstract The purpose of this study is to investigate and analyze the effect of product attributes on a blackberry smartphone purchasing decisions on the management students of the Faculty of Economics of University of North Sumatra, Medan. The data used in this study is primary data and secondary data. Primary data obtained from questionnaires. Secondary data obtained from the study of the documentation of the literature books, journals, magazines, and internet pages that are relevant to the research. The population in this study were all students of the Faculty of Economics, University of Management North Sumatra 2007-2012 generation using blackberry smartphone with a population not known and was  obtained a  sample of 97 people. Sampling technique was accidental sampling technique. Method of data analysis used in this study is to model the multiple regression analysis. Hypothesis testing using a significance level of 10%. The results showed that the product attributes which consists of quality, features, design, brand and label has a positive and significant impact on purchasing decisions blackberry smartphone management students of the Faculty of Economics at the University of North Sumatra. Keywords: Product Attributes and Purchase Decision.